2013
DOI: 10.36457/gizindo.v36i2.142
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran Konsumsi Zat Gizi Anak Umur 6 Bulan – 12 Tahun Di Indonesia

Abstract: Prevalensi gangguan gizi pada anak di Indonesia terutama stunting masih cukup tinggi dan menempati posisi kelima terbesar di dunia. Penyebab multi sektoral gangguan gizi termasuk makanan, kesehatan dan pola asuh. Di tingkat individu, penyebab langsung gangguan gizi tersebut adalah masih rendahnya kuantitas konsumsi makanan dan rendahnya kualitas bahan makanan yang dikonsumsi, serta adanya penyakit infeksi. Tulisan ini bertujuan untuk mengetahui konsumsi makanan anak di Indonesia. Studi SEANUTS dilakukan di 48 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
4
0
3
Order By: Relevance
“…29 In Indonesia, research conducted in 48 districts in urban and rural areas showed that with increasing age, nutrient insufficiency is increasing from 8 month to 12 year old. 30 We found it interesting that protein consumption in both the stunted and non-stunted groups was above sufficient, while the carbohydrate adequacy, especially in the stunted group, was insufficient. Likewise, the stunted group had significantly more children with insufficient fat intake than did the non-stunted group.…”
Section: Discussionmentioning
confidence: 73%
“…29 In Indonesia, research conducted in 48 districts in urban and rural areas showed that with increasing age, nutrient insufficiency is increasing from 8 month to 12 year old. 30 We found it interesting that protein consumption in both the stunted and non-stunted groups was above sufficient, while the carbohydrate adequacy, especially in the stunted group, was insufficient. Likewise, the stunted group had significantly more children with insufficient fat intake than did the non-stunted group.…”
Section: Discussionmentioning
confidence: 73%
“…This was also true for vitamin A, vitamin C, folic acid, calcium, and phosphorus. 58 Low maternal education, low socioeconomic status, and living in a rural area increased the proportion of insufficient nutrient intake. 58 Considering the harmful effects and the high proportion of nutritional insufficiency in our setting, specific public health interventions are needed to improve children's nutritional sufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian ini melibatkan 28 subjek anak penyandang epilepsi dengan median usia 5,1 tahun (1,(6)(7)(8)(9)(10)(11)9), dengan rerata durasi terapi 31,04±19,47 bulan yang kemudian didapatkan rerata kadar asam folat 19,53 ± 6,47 ng/ml. Tiga belas dari 28 subjek penelitian memiliki klinis kejang tidak terkontrol, dengan frekuensi kejang 2-90 kali per bulan.…”
Section: Hasilunclassified
“…Kejadian defisiensi asam folat di Indonesia terutama pada anak penyandang epilepsi belum diketahui, tetapi dari data tahun 2013 diketahui kecukupan konsumsi asam folat anak Indonesia masih di bawah angka kecukupan gizi yakni 44-77%, dan terbanyak pada kelompok usia 9-12 tahun. 6 Dengan demikian, penyandang epilepsi berisiko lebih besar memiliki kadar asam folat yang rendah.…”
unclassified